1989
DOI: 10.1073/pnas.86.23.9611
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a genetically reconstituted high-affinity system for serotonin transport.

Abstract: By transfecting mouse fibroblast L-M cells with human genomic DNA, we have established and identified several clonal cell lines that stably express a high-affinity serotonin (5-HT)-uptake mechanism absent in untransfected host cells. One such cell line, L-S1, possesses features of 5-[3H]HT uptake similar to those previously characterized in the central nervous system and blood platelets: (i) specificity for 5-HT; (ii) antagonism by imipramine, a known inhibitor of high-affinity 5-HT uptake; (ii) both Nal and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It was previously shown that L_S1 cells exhibit a saturable velocity profile in transporting 5_ [ÅH]HT, characterized by Michaelis-Menten parameters (Km = 0·39 ± 0·10 ìÒ, Vmax = 2·14 ± 0·55 pmol mg¢ min¢, nH = 0·95 ± 0·09) which are highly comparable to those of other serotonin transport systems (Chang et al 1989(Chang et al , 1996. The apparent lack of ligand co-operativity during transport agrees with the observed lack of ligand co-operativity during binding to the transport complex, and further suggests that each cycle of 5_HT transport translocates one 5_HT molecule.…”
Section: Ion Dependences Of 5_[åh]ht Uptakementioning
confidence: 69%
See 4 more Smart Citations
“…It was previously shown that L_S1 cells exhibit a saturable velocity profile in transporting 5_ [ÅH]HT, characterized by Michaelis-Menten parameters (Km = 0·39 ± 0·10 ìÒ, Vmax = 2·14 ± 0·55 pmol mg¢ min¢, nH = 0·95 ± 0·09) which are highly comparable to those of other serotonin transport systems (Chang et al 1989(Chang et al , 1996. The apparent lack of ligand co-operativity during transport agrees with the observed lack of ligand co-operativity during binding to the transport complex, and further suggests that each cycle of 5_HT transport translocates one 5_HT molecule.…”
Section: Ion Dependences Of 5_[åh]ht Uptakementioning
confidence: 69%
“…Novel models of such transport systems have been generated by transfecting human genomic DNA into mouse fibroblast L_M cells, resulting in clonal cell lines each of which stably manifests a high-affinity neurotransmitter uptake system (Chang et al 1989). This approach has yielded two clonal cell lines, L_S1 and L_S2, which possess physiological and pharmacological characteristics of 5_ [ÅH]HT transport that are comparable to other systems of 5_HT transport (Frnka et al 1991;Chang et al 1993).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations